Effect of Silicon on Abrasive Wear Behavior of Heat-Treated 16% Cr - 2% Mo Cast Iron - โคสะสุ พิสิฐชัย; อินธิเดช สุดสาคร (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2019)
In this research, the effect of silicon (Si) on abrasive wear behavior of heat-treated 16 wt% Cr - 2 wt% Mo (as shown by %) cast iron was investigated. The specimens with 0.5 - 2.0 % Si were prepared. The specimens were annealed at 900 oC and then, hardened from 1,050 oC by oil quenching. The hardened specimens were tempered at 450, 500 and 550 oC, respectively. The abrasive wear resistance of specimens was evaluated using Suga abrasion tester. It was found that the linear relation between wear loss and wear distance was obtained in all specimens. The wear rate (Rw, mg/m) of specimen lowered as the hardness rose. The as-hardened specimens showed lower Rw value than tempered specimen did. In each heat treatment condition, the Rw value decreased progressively in the 1.5 % Si specimen and then increased gradually as the Si content increased. In the tempered state, the lowest Rw was obtained in the specimen tempered at 500 oC and the highest value of Rw was obtained in the specimen tempered at 550 oC. The specimen with 1.5 % Si was found to provide the lowest Rw or largest wear resistance.